2020
DOI: 10.1093/clinchem/hvaa213
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Serial Profiling of SARS-CoV-2 Antigens and Antibodies in Plasma to Understand Disease Progression in COVID-19 Patients with Severe Disease

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected over 21 million people worldwide since August 16, 2020. Compared to PCR and serology tests, SARS-CoV-2 antigen assays are underdeveloped, despite their potential to identify active infection and monitor disease progression. Methods We used Single Molecule Array (Simoa) assays to quantitatively detect SARS-CoV-2 spike, S1 subunit, and nucleoca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
173
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(198 citation statements)
references
References 19 publications
13
173
1
Order By: Relevance
“…Although we could not directly compare our results with this study due to a difference in comparison group, both studies highlight the immune response led by neutrophils in COVID-19 patients. The other study, performed by Ogata et al, used the Simoa™ assay to measure viral antigens and antibodies in plasma 31 . In this study, antibody-coated beads were used to detect and quantify viral fragments in the blood of COVID-19 patients, suggesting possibility of using this assay for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Although we could not directly compare our results with this study due to a difference in comparison group, both studies highlight the immune response led by neutrophils in COVID-19 patients. The other study, performed by Ogata et al, used the Simoa™ assay to measure viral antigens and antibodies in plasma 31 . In this study, antibody-coated beads were used to detect and quantify viral fragments in the blood of COVID-19 patients, suggesting possibility of using this assay for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, it requires a specialized instrument (HD-X Analyzer (Quanterix)) that is quite expensive. 240 Simultaneous IgG/IgM/unreported antigen detection of SARS-CoV-2 was achieved on an integrated microfluidic fluorescence immunoassay system. 78 Another group quantified SARS-CoV-2 N protein, IgG, IgM, and C-reactive protein in serum and saliva using a multiplexed electrochemical graphene-based platform called SARS-CoV-2 RapidPlex.…”
Section: Future Directionsmentioning
confidence: 99%
“…Head-to-head comparisons of AD test performance for SARS-CoV-2 detection are scarce. The majority of the studies only included few patients, precluding a wide characterization of the “real-life” performance of these devices [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Recently, a Cochrane study found an average sensitivity of only 56.2% (95% confidence interval (CI): 29.5–79.8%) for rapid AD (RAD) tests [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a Cochrane study found an average sensitivity of only 56.2% (95% confidence interval (CI): 29.5–79.8%) for rapid AD (RAD) tests [ 11 ]. Independent reporting of automated AD test performance remains limited [ 18 ].…”
Section: Introductionmentioning
confidence: 99%